Solid Additive-Assisted Layer-by-Layer Processing for 19% Efficiency Binary Organic Solar Cells - Ding, Guanyu; Chen, Tianyi; Wang, Mengting; Xia, Xinxin; He, Chengliang; Zheng, Xiangjun; Li, Yaokai; Zhou, Di; Lu, Xinhui; Zuo, Lijian; Xu, Zhikang; Chen, Hongzheng (Nano-Micro Letters, 2023)
Morphology is of great significance to the performance of organic solar cells (OSCs), since appropriate morphology could not only promote the exciton dissociation, but also reduce the charge recombination. In this work, we have developed a solid additive-assisted layer-by-layer (SAA-LBL) processing to fabricate high-efficiency OSCs. By adding the solid additive of fatty acid (FA) into polymer donor PM6 solution, controllable pre-phase separation forms between PM6 and FA. This intermixed morphology facilitates the diffusion of acceptor Y6 into the donor PM6 during the LBL processing, due to the good miscibility and fast-solvation of the FA with chloroform solution dripping. Interestingly, this results in the desired morphology with refined phase-separated domain and vertical phase-separation structure to better balance the charge transport /collection and exciton dissociation. Consequently, the binary single junction OSCs based on PM6:Y6 blend reach champion power conversion efficiency (PCE) of 18.16% with SAA-LBL processing, which can be generally applicable to diverse systems, e.g., the PM6:L8-BO-based devices and thick-film devices. The efficacy of SAA-LBL is confirmed in binary OSCs based on PM6:L8-BO, where record PCEs of 19.02% and 16.44% are realized for devices with 100 and 250 nm active layers, respectively. The work provides a simple but effective way to control the morphology for high-efficiency OSCs and demonstrates the SAA-LBL processing a promising methodology for boosting the industrial manufacturing of OSCs. Highlights: 1 A solid additive-assisted layer-by-layer (SAA-LBL) processing was developed to facilitate the inter-diffusion between polymer donor and acceptor and optimize the morphology of quasi-planar heterojunction for high-performance organic solar cells (OSCs). 2 The pre-phase separation between fatty acid and polymer donor, easily tuned via controlling the cohesive energy, is critical to form the desired vertical phase-separation morphology. 3 The SAA-LBL is generally applicable to various OSC systems, and enables the record efficiency of 19.02% among the binary OSCs.